CURRICULAR ENVIRONMENTALIZATION IN PEDAGOGY COURSES AT HIGHER EDUCATION INSTITUTIONS IN THE STATE OF GOIÁS: CHALLENGES AND PROPOSALS - Galdino da Silva, Fernanda; Peixoto, Josana de Castro (CIPEEX, 2022)
THE MAIN THEME REFERS TO THE ANALYSIS OF CURRICULAR ENVIRONMENTALIZATION ASSOCIATED WITH ENVIRONMENTAL EDUCATION STUDIES AS A SITUATION ANALYSIS. TEACHERS€™ TRAINING IN BRAZIL, ESPECIALLY IN THE PEDAGOGY COURSE, FOR AT LEAST TWO DECADES, HAS BEEN SEEKING TO OVERCOME HISTORICAL AND THEORETICAL DILEMMAS OF ITS CURRICULUM DUE TO THE NEW TRAINING DEMANDS OF ITS UNDERGRADUATES. SOME PARTS OF THE SOCIETY STRONGLY TEND TO ATTRIBUTE TO FORMAL EDUCATION, AND ESPECIALLY TO EDUCATORS, THE RESPONSIBILITY TO BEGIN THE PROCESSES OF DESIRABLE CHANGES, BY TEACHING NEW GENERATIONS MORE POSITIVE ATTITUDES TOWARDS SOCIAL ENVIRONMENTAL ISSUES. THE ANALYSIS OF PEDAGOGICAL PROJECTS, RELATED TO COORDINATORS€™ AND PROFESSORS€™ SPEECH AND PRACTICE OF PEDAGOGY COURSES, BECOMES RELEVANT SINCE IT WILL CHARACTERIZE THE PROFILE AND CURRENT CONDITIONS OF TEACHERS€™ TRAINING WHO WILL WORK IN EARLY CHILDHOOD EDUCATION. THE CHALLENGES AND PROPOSALS TOWARDS THE INCLUSION OF THE ENVIRONMENTAL THEME IN THE INITIAL TEACHERS€™ TRAINING, HIGHLIGHTING THE CURRICULAR ENVIRONMENTALIZATION MOVEMENT, IS STILL A CHALLENGE, SINCE IT COMPRISES THE INCLUSION OF KNOWLEDGE, CRITERIA, SOCIAL, ETHICAL, AESTHETIC AND ENVIRONMENTAL VALUES IN COLLEGE CURRICULUM. IN ORDER TO KNOW WHAT HAS ALREADY BEEN PRODUCED ON THE INCLUSION OF ENVIRONMENTAL EDUCATION IN THE BEGINNING OF EDUCATORS TRAINING, A SURVEY OF PUBLISHED STUDIES WAS CARRIED OUT, WITH A QUERY TO THE DATABASE OF THE DIGITAL LIBRARY OF THESES AND DISSERTATIONS (BDTD) OF THE CENTER FOR IMPROVEMENT AND RESEARCH OF HIGHER EDUCATION - CAPES. IN THIS SURVEY, THE DISSERTATIONS AND THESES DEFENDED FROM 2015 TO 2022 WERE CONSIDERED. THE ENVIRONMENTAL THEME IN THE PEDAGOGY COURSE WOULD BE MORE APPROPRIATE WHEN INSERTED IN A DISCIPLINARY OR INTERDISCIPLINARY WAY AND IT WAS VERIFIED THAT, ALTHOUGH THERE IS A CONSENSUS AMONG THE SUBJECTS REGARDING THE NEED FOR ITS INCLUSION, THERE ARE, ON THE OTHER HAND, DISAGREEMENTS REGARDING THE €ŒOPERATIONALIZATION€ OF IT. THERE ARE ALSO LIMITATIONS IMPOSED ON ENVIRONMENTAL EDUCATION IN THE CURRICULUM, SUCH AS: TEACHER TRAINING, SPECIFICITIES OF THE DISCIPLINES, FRAGMENTATION OF SPACE/TIME, AND CONTRADICTIONS RELATED TO THE SYSTEM. THE NEED FOR RESEARCH ON THIS PEDAGOGY-ENVIRONMENTAL EDUCATION RELATIONSHIP FOR THE STATE OF GOIS IS CONCLUDED, SINCE THE INTERDISCIPLINARY APPROACH TO THE CURRICULUM IS ADDED TO THE STILL TRADITIONAL SPEECH WITH FEW ENVIRONMENTAL PROJECTIONS.